2017
DOI: 10.5935/1980-6906/psicologia.v19n3p226-241
|View full text |Cite
|
Sign up to set email alerts
|

Initial literacy: Influence of phonemic awareness and teaching method

Abstract: This longitudinal study investigates the importance of two methods for the success of the learning of reading and spelling and for the development of the phonemic awareness (PA) ability. It also verifies the contribution of PA and its predictive capacity for literacy learning in Brazilian Portuguese (PB). Two groups of children who started the first year (Mage = 5;10 years), one from a school that adopted a phonic method and the other from a school that adopted a nonphonic method, were followed until the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
(27 reference statements)
0
8
0
3
Order By: Relevance
“…When the child is able to break the sounds of words from the words that are spoken, then he will then learn to connect the sounds of the words with the symbols written in the language. The phonological awareness is stronger predictor for reading (Godoy, Pinheiro, & Citoler, 2017). Students have problem in phonological awareness, stronger predict have problem in reading.…”
Section: Resultsmentioning
confidence: 84%
“…When the child is able to break the sounds of words from the words that are spoken, then he will then learn to connect the sounds of the words with the symbols written in the language. The phonological awareness is stronger predictor for reading (Godoy, Pinheiro, & Citoler, 2017). Students have problem in phonological awareness, stronger predict have problem in reading.…”
Section: Resultsmentioning
confidence: 84%
“…As habilidades de leitura e de escrita são tarefas complexas que precisam de treino formal. Os estudos apontam (Andrade et al, 2014;Godoy et al, 2017;Seabra & Dias, 2011) a eficiência do Método Fônico no ensino dessas habilidades, uma vez que o método privilegia o ensino explícito e sistemático das letras e dos fonemas, favorecendo habilidades essenciais ao desenvolvimento da CF e da associação grafema-fonema, necessárias para a apropriação do código alfabético e, consequentemente, para a aprendizagem da leitura e escrita .…”
Section: Introductionunclassified
“…them (Bravo Valdivieso, 2016;De la Calle, Guzmán-Simón, & García-Jiménez, 2018;Gutiérrez, 2017;Jiménez, 2009;Perfetti & Stafura, 2014). Early reading usually covers the first two years of formal education for reading transparent languages, being longer in the case of opaque languages (Caravolas et al, 2019;Godoy, Pinheiro, & Citoler, 2017;Müller & Brady, 2001). This means that languages with greater correspondence between their phonemes and graphemes tend to be associated with faster learning rates for early decoding skills (Caravolas et al, 2019;Diuk & Ferroni, 2013).…”
mentioning
confidence: 99%
“…Several studies have shown that some of the skills acquired in early reading favor reading performance for text comprehension. These skills are phonemic awareness, segmentation of syllables and words, naming speed, spelling of nonwords and alphabet knowledge (Diamanti et al, 2017;Godoy et al, 2017;Goswami, 2002;Gutiérrez, 2017;Ouellette & Sénéchal, 2017;Stappen & Van Reybroeck, 2018). Some studies suggest that phonological and phonemic awareness are the most important predictors of reading performance in the first years of this learning, while naming speed and reading of words and nonwords are better predictors of advanced learning focused on reading comprehension (Caravolas et al, 2019;Diuk & Ferroni, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation